Kp‐10 promotes bovine mammary epithelial cell proliferation by activating GPR54 and its downstream signaling pathways. Issue 5 (17th October 2019) - Li, Yanwei; Cao, Yu; Wang, Jiaxin; Fu, Shoupeng; Cheng, Ji; Ma, Lijun; Zhang, Qing; Guo, Wenjin; Kan, Xingchi; Liu, Juxiong
Abstract: It has been reported that the proliferation and apoptosis of mammary epithelial cells affect milk production. Therefore, ensuring adequate mammary epithelial cells is expected to enhance milk production. This study is devoted to studying the effects of kisspeptin‐10 (Kp‐10), a peptide hormone composed of 10 amino acids, on bovine mammary epithelial cell (bMEC) proliferation and exploring the underlying mechanism of its action. bMECs were treated with various concentrations of Kp‐10 (1, 10, 100, and 1, 000 nM), and 100 nM Kp‐10 promoted the proliferation of the bMECs. Kp‐10 promoted the cell cycle transition from G1 to the S and G2 phases, increased the protein levels of Cyclin D1 and Cyclin D3, and reduced the expression levels of the p21 gene. This study also showed that inhibition of G protein‐coupled receptor 54 (GPR54), AKT, mTOR, and ERK1/2 reduced the proliferation of the bMECs that had been induced by Kp‐10. In addition, Kp‐10 decreased the complexes formed by Rb and E2F1 and increased the expression levels of the E2F1 target genes. These results indicate that Kp‐10 promotes bMEC proliferation by activating GPR54 and its downstream signaling pathways. Abstract : The proliferation of bovine mammary epithelial cells can increase milk production. We found that Kisspeptin‐10 promotes the proliferation of bovine mammary epithelial cells by activating the GPR54 and its downstream signaling pathways.